An experimental study on the effect of the sele-selected reading activities on Hai Phong private University's English Non-Majors' reading proficiency - Nguyễn, Việt Anh (ĐHNN, 2017)
How to teach reading effectively is becoming a big matter in universities. In order to promote students’ activeness as well as to enhance their reading proficiency, “an experimental study on the effect of the self-selected reading activities on Haiphong Private University’s English non-majors’ reading proficiency” was carried out.